Evaluación técnico-financiera del potencial de los proyectos de producción offshore en la cuenca Sinú- offshore del caribe colombiano y el dimensionamiento de volúmenes de hidrocarburos mínimos económicos (2017)
The main objective of this work is the Technical Financial Assessment of the potential of offshore production projects and the dimensioning of minimum economic hydrocarbon volumes. This work comprises a progressive development of different stages that starts from the bibliographical collection and selection of geological analogues, through the processing of the petrophysical data obtained in the simulators, sensitivities of pipe diameters, production of different production plates for different volumes of Hydrocarbons, selection of offshore production facilities, to an analysis of the results that allow to determine the minimum economic hydrocarbon volumes.